2019
DOI: 10.7717/peerj.6652
|View full text |Cite
|
Sign up to set email alerts
|

IOCBIO Sparks detection and analysis software

Abstract: Analysis of calcium sparks in cardiomyocytes can provide valuable information about functional changes of calcium handling in health and disease. As a part of the calcium sparks analysis, sparks detection and characterization is necessary. Here, we describe a new open-source platform for automatic calcium sparks detection from line scan confocal images. The developed software is tailored for detecting only calcium sparks, allowing us to design a graphical user interface specifically for this task. The software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…We examined spontaneous Ca 2+ sparks since these events occur almost exclusively at dyads ( Louch et al, 2013 ), where RyR arrangements appear to be sensitive to β-AR stimulation ( Figure 1f ). Previous work has shown that acute β-AR activation increases the frequency of spontaneous Ca 2+ sparks, while diverse effects on spark geometry are reported ( Laasmaa et al, 2019 ; Tanaka et al, 1997 ; Viatchenko-Karpinski and Györke, 2001 ). We hypothesized, however, that RyR dispersion during prolonged β-AR stimulation would slow spark kinetics and increase Ca 2+ leak, as released Ca 2+ propagates between multiple clusters.…”
Section: Resultsmentioning
confidence: 99%
“…We examined spontaneous Ca 2+ sparks since these events occur almost exclusively at dyads ( Louch et al, 2013 ), where RyR arrangements appear to be sensitive to β-AR stimulation ( Figure 1f ). Previous work has shown that acute β-AR activation increases the frequency of spontaneous Ca 2+ sparks, while diverse effects on spark geometry are reported ( Laasmaa et al, 2019 ; Tanaka et al, 1997 ; Viatchenko-Karpinski and Györke, 2001 ). We hypothesized, however, that RyR dispersion during prolonged β-AR stimulation would slow spark kinetics and increase Ca 2+ leak, as released Ca 2+ propagates between multiple clusters.…”
Section: Resultsmentioning
confidence: 99%
“…11.1). Ca 2+ transients were analyzed using ImageJ software but LCRs were analyzed using a homemade software written on R (olivierbortolotti/lcr-analysis-san (github.com), accessed on 22 November 2021), inspired by IOCBIO sparks detection and analysis software [ 32 ]. Since cells have not been permeabilized, the software measured LCR parameters after suppressing the AP-induced Ca 2+ transient to allow an accurate comparison between dormant and firing SANC.…”
Section: Methodsmentioning
confidence: 99%
“…1f). Previous work has shown that acute β-AR activation increases the frequency of spontaneous Ca 2+ sparks, while diverse effects on spark geometry are reported 26-28 . We hypothesized, however, that RyR dispersion during prolonged β-AR stimulation would slow spark kinetics and increase Ca 2+ leak, as released Ca 2+ propagates between multiple clusters.…”
Section: Resultsmentioning
confidence: 99%